Changes in the Activity of Clotting Factors in Relation to the Onset of Platelet Clumping and Fibrin Formation - Mustard, J. F; Hoeksema, T. D (Thrombosis and Haemostasis, 1962)
The relationship has been studied between changes in clotting factors and the onset of platelet clumping and fibrin formation during the clotting of normal and pathological blood. In normal blood, glass activation factor activity, factor IX activity and platelet adhesiveness were found to increase prior to the onset of platelet clumping. There was no change in factor VIII or factor V activity until after the onset of platelet clumping. At about this point, detectable thrombin formation occurred and this was shortly followed by the onset of macroscopic fibrin formation. After fibrin formation, there was an increase in factor VII activity and a fall in factor IX activity. This fall in factor IX activity did not occur during the clotting of platelet poor normal plasma.During the clotting of haemophilia A blood, there were similar changes to those seen with normal blood, except that the time of onset of platelet clumping was greatly delayed and the degree of change was often much less. When haemophilia B blood clotted, there was a temporary increase in factor IX activity at the point of platelet clumping which was closely followed by a marked decrease in factor IX activity. This decrease in factor IX activity was not found during the clotting of platelet poor haemophilia B plasma. Another difference was that factor VII activity decreased following the onset of fibrin formation.In PTA blood the major difference from normal appeared to be a delayed activation of factor IX.